Say‐Barber‐Biesecker‐Young‐Simpson syndrome and Genitopatellar syndrome: Lumping or splitting?. Issue 2 (25th January 2018) - Lonardo, F.; Lonardo, M.S.; Acquaviva, F.; Della Monica, M.; Scarano, F.; Scarano, G.
Abstract : The Say‐Barber‐Biesecker‐Young‐Simpson variant of Ohdo syndrome (SBBYSS) and Genitopatellar syndrome (GTPTS) are 2 rare but clinically well‐described diseases caused by de novo heterozygous sequence variants in the KAT6B gene. Both phenotypes are characterized by significant global developmental delay/intellectual disability, hypotonia, genital abnormalities, and patellar hypoplasia/agenesis. In addition, congenital heart defects, dental abnormalities, hearing loss, and thyroid anomalies are common to both phenotypes. This broad clinical overlap led some authors to propose the concept of KAT6B spectrum disorders. On the other hand, some clinical features could help to differentiate the 2 disorders. Furthermore, it is possible to establish a genotype‐phenotype correlation when considering the position of the sequence variant along the gene, supporting the notion of the 2 disorders as really distinct entities. Abstract : Say‐Barber‐Biesecker‐Young‐Simpson variant of Ohdo syndrome (SBBYSS) and Genitopatellar syndrome (GTPTS) are 2 rare but clinically well‐described diseases. Some authors propose to unify them under a single denomination (KAT6B‐related disorders) because they may have many clinical features in common and are caused by sequence variants in the same gene. We believe that from a clinical point of view the facial phenotype of the patients with SBBYSS is striking enough to consider it appropriate to still maintain a distinction.